Spontaneous per rectal passage of a gossypiboma - Butt, Usman Ismat; Shahid, Anayza Fatima; Siddique, Muhammad Usman; Ali, Abrar Ashraf; Butt, Nauman Ismat (International Journal of Pathology, 2026)
Background: A retained foreign body after a surgical intervention, known as gossypiboma, is a rare yet devastating complication. Spontaneous per-rectal passage of such a foreign body has been rarely reported. Case Report: We present such a case of a 30-year-old female who underwent an elective caesarean section and presented eight months later with mild abdominal discomfort, a palpable lump in the right lower quadrant and low-grade fever. Imaging suggested a retained abdominal sponge. The patient subsequently experienced spontaneous per rectal passage of the sponge, leading to complete resolution of symptoms without surgical intervention. Conclusion: This case highlights the rare occurrence of spontaneous transmural migration and expulsion of gossypiboma. Clinicians should consider gossypiboma in the differential diagnosis of postoperative abdominal masses, even in elective surgeries with no apparent risk factors. Strict adherence to surgical safety protocols remains essential to prevent such avoidable complications.